Abai and Ethno-pedagogy. - Zeinolla, Zh. (Journal of Oriental Studies, 2016)
This article particularly describes about how to teach and how to educate children in the examples of the great Kazakh thinker, educator and philosopher Abai Kunanbayev. Also describes that he was one of the great teachers of the world who left valuable pedagogical works about teacher’s formation.